ANALISIS PENERAPAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI SDN PASIRKAMUNING I KECAMATAN TELAGASARI KABUPATEN KARAWANG - Rizal, Bachruddin; Yadi Fahmi Arifudin; Masykur H. Mansyur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Currently being implemented under the Merdeka Curriculum as a character education initiative is The Pancasila Student Profile Strengthening initiative. Finding out how the Pancasila Student Profile may promote national character and the methods teachers use to implement it to assist students develop moral character are the goals of this research. Class V of SDN Pasirkamuning I Kec. Telagasari Kab. Karawang was the site of this study. This kind of investigate, which portrays how teaches actualized the Pancasila Understudy Profile and the methodologies they utilized to do so, is subjective in nature. Three methods of gathering data are employed: documentation, interviews, and observation. The Project for Strengthening Pancasila Student Profiles employed project-based learning and habituation, which emphasizes character development in students, as techniques employed by instructors, according to observational data. Teachers have done a good job of implementing the strategy, according to research findings. Teachers must be imaginative in their lesson planning in order to apply this strategy effectively. The family and social surroundings, in addition to the function of the instructor, have a significant effect in how children grow as individuals.